Increasing resilience of smallholder farmers to climate change through multiple adoption of proven climate-smart agriculture innovations. Lessons from Southern Africa. (1st February 2019) - Makate, Clifton; Makate, Marshall; Mango, Nelson; Siziba, Shephard
Abstract: Conservation agriculture, drought tolerant maize, and improved legume varieties are key climate change management strategies for smallholder farmers in southern Africa. Their complementary efforts in adaptation to climate change are sternly important for farm productivity and income. This study evaluates factors explaining individual and multiple adoption of climate change management strategies and their differential impacts on productivity and income using a sample of 1172 smallholder farmers from Malawi and Zimbabwe. The study employs multinomial logistic regression to evaluate factors of individual and multiple adoption and regression adjustment with inverse probability weighting to evaluate impacts of the different adoption regimes on farm productivity and income. The results show that multiple adoption of innovations is mostly explained by access to key resources (credit, income and information), level of education and size of land owned by the farmer. More so, the concurrent adoption of conservation agriculture, stress adapted legume varieties and drought tolerant maize has far greater dividends on productivity and income than when considered individually. However, impacts of multiple adoption of the practices are not entirely uniform across different geographic regions and gender. Results suggest that effective institutional and policy efforts targeted towards reducing resource constraints that inhibit farmers' capacity to adopt complementary climate-smart agriculture packages such as conservation agriculture, drought tolerant maize and improved legume varieties must be gender sensitive and context specific. Highlights: Access to land, credit, information and education enhance multiple climate smart agricultural (CSA) innovations adoption. Multiple adoption of CSA innovations yields greater productivity and income dividends than individual adoption. Disparities in impact of multiple CSA adoption are evident by gender and geographic location. Gender sensitive policy and institutional efforts towards reducing resource access constraints for CSA should be a priority.